Modulating fluid intelligence performance through combined cognitive training and brain stimulation. (September 2018) - ,; Brem, Anna-Katharine; Kadosh, Roi Cohen; Mansfield, Karen; Yeung, Nick; Plessow, Franziska; Santarnecchi, Emiliano; Pascual-Leone, Alvaro; Almquist, Jessamy Norton-Ford; Dillard, Michael; Orhan, Umut; Mathan, Santosh; et al.
Abstract: It is debated whether cognitive training of specific executive functions leads to far transfer effects, such as improvements in fluid intelligence ( Gf ). Within this context, transcranial direct current stimulation and recently also novel protocols such as transcranial random noise and alternating current stimulation are being investigated with regards to their ability to enhance cognitive training outcomes. We compared the effects of four different transcranial electrical brain stimulation protocols in combination with nine daily computerized training sessions on Gf . 82 participants were randomly assigned to receive transcranial direct current stimulation (tDCS), random noise stimulation (tRNS), multifocal alternating current stimulation at 40 Hz (mftACS), or multifocal tDCS (mftDCS) in combination with an adaptive and synergistic executive function (EF) training, or to a no-contact control group. EF training consisted of gamified tasks drawing on isolated as well as integrated executive functions (working memory, inhibition, cognitive flexibility). Transfer was assessed with a combined measure of Gf including three established tests (Bochumer Matrizentest - BOMAT, Raven's Advanced Progressive Matrices - RAPM, and Sandia Matrices). We found significant improvements in Gf for the tDCS, mftDCS, and tRNS groups when compared with the no-contact group. In contrast, the mftACS group did not improve significantly and showed a similar pattern as the no-contact group. Mediation analyses indicated that the improvement in Gf was mediated through game progression in the mftDCS and tRNS group. Electrical brain stimulation in combination with sustained EF training can lead to transfer effects in Gf, which are mediated by training progression. Highlights: Cognitive training combined with tES leads to far transfer effects on Gf . tDCS, tRNS, and mftDCS were similarly effective. mftACS showed a similar pattern as the no-contact group. Improvement in Gf was mediated through training progression in mftDCS and tRNS.